Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.